2020
DOI: 10.1155/2020/1426401
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Arteritis and Vision Loss in Microscopic Polyangiitis: A Case Report and Literature Review

Abstract: Microscopic polyangiitis (MPA) is an idiopathic autoimmune disease characterized by systemic vasculitis. While the lungs and kidneys are the major organs affected by MPA, it is known to involve multiple organ systems throughout the body. Temporal artery involvement is a very rare finding in MPA. This report presents a patient whose initial presentation was consistent with giant cell arteritis but was ultimately found to have microscopic polyangiitis. It highlights the importance of considering alternative type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Due to the diagnosis of MPA, ophthalmology attributed the vision loss to small vessel vasculitis instead. However, there have been 15 reported cases of concurrent GCA (a large vessel vasculitis) in MPA in the literature [ 4 ]. Temporal artery biopsy was not performed, so we do not have a pathological verification for the cause of her vision loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the diagnosis of MPA, ophthalmology attributed the vision loss to small vessel vasculitis instead. However, there have been 15 reported cases of concurrent GCA (a large vessel vasculitis) in MPA in the literature [ 4 ]. Temporal artery biopsy was not performed, so we do not have a pathological verification for the cause of her vision loss.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the prevalence of this disease is 1.3 per 100,000 persons and typically affects middle-aged Caucasian men or women equally [1]. Though renal symptoms predominate in patients with this disease, presentations of MPA affecting other organs have been described [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“… 7 15 A recently published case of an elderly man with bitemporal headache, jaw claudication, right-eye vision loss, and severe glomerulonephritis with positive p-ANCA showed that MPA can insult temporal and ophthalmic arteries. 8 A MPA case of a 65-year-old patient with unilateral temporal headache, scalp tenderness, jaw claudication, mononeuritis and mild glomerulonephritis has seen the light some years ago. 11 Tanaka et al reported a case of a 81-year-old man with bilateral temporal headache, fever, interstitial pneumonia and glomerulonephritis, with a positive TAB for vasculitis, that turned out to be MPA.…”
Section: Discussionmentioning
confidence: 99%